Bidang kuasa mahkamah perusahaan: satu kritikan - Kamal Halili Hassan, (Fakulti Undang - Undang, 2004)

(untitled)
This article seeks to discuss the jurisdictions of the Industrial Court as provided in the Industrial Relations Act 1967. The jurisdictions of the Industrial Court are limited, as they have to be derived from the four corners of the Act. Basically, the jurisdictions are in regards to adjudication, interpretation, variance of an enforcement of the Award of the Court or the ratified Collective Agreements. One of the essential and special characteristics of the Industrial Court is that, in exercising its judicial functions, it must act in accordance with the principles of equity, good conscience, substantial merits of the case and not to be bound by technicalities. As such, the operation of the Court this for has been informal or less technical. This article also discusses the inherent jurisdiction of the Industrial Court, whether it has one or not. It also discusses the issue of contempt of court. It has been suggested that the rule of contempt of court ought to be strengthened to enhance the credibility of the Court